Unilateral Quadriceps Fatigue Induces Greater Impairments of Ipsilateral versus Contralateral Elbow Flexors and Plantar Flexors Performance in Physically Active Young Adults - Whitten, Joseph H.D. (J Sports Sci Med, 2021)
Non-local muscle fatigue (NLMF) studies have examined crossover impairments of maximal voluntary force output in non-exercised, contralateral muscles as well as comparing upper and lower limb muscles. Since prior studies primarily investigated contralateral muscles, the purpose of this study was to compare NLMF effects on elbow flexors (EF) and plantar flexors (PF) force and activation (electromyography: EMG). Secondly, possible differences when testing ipsilateral or contralateral muscles with a single or repeated isometric maximum voluntary contractions (MVC) were also investigated. Twelve participants (six males: (27.3 ± 2.5 years, 186.0 ± 2.2 cm, 91.0 ± 4.1 kg; six females: 23.0 ± 1.6 years, 168.2 ± 6.7 cm, 60.0 ± 4.3 kg) attended six randomized sessions where ipsilateral or contralateral PF or EF MVC force and EMG activity (root mean square) were tested following a dominant knee extensors (KE) fatigue intervention (2×100s MVC) or equivalent rest (control). Testing involving a single MVC (5s) was completed by the ipsilateral or contralateral PF or EF prior to and immediately post-interventions. One minute after the post-intervention single MVC, a 12×5s MVCs fatigue test was completed. Two-way repeated measures ANOVAs revealed that ipsilateral EF post-fatigue force was lower (-6.6%, p = 0.04, d = 0.18) than pre-fatigue with no significant changes in the contralateral or control conditions. EF demonstrated greater fatigue indexes for the ipsilateral (9.5%, p = 0.04, d = 0.75) and contralateral (20.3%, p < 0.01, d = 1.50) EF over the PF, respectively. There were no significant differences in PF force, EMG or EF EMG post-test or during the MVCs fatigue test. The results suggest that NLMF effects are side and muscle specific where prior KE fatigue could hinder subsequent ipsilateral upper body performance and thus is an important consideration for rehabilitation, recreation and athletic programs.